INCREASING ADOLESCENTS’ KNOWLEDGE OF MARRIAGE AGE MATURATION (PUP) THROUGH COMIC MEDIA: AN EXPERIMENTAL STUDY - Sarliana; Admasari, Yuli; Asriwidyayanti (The Indonesian Journal of Public Health, 2024)
Introduction: Reducing the incidence of child marriage is a component of the national medium-term plan (RPJMN) for 2020-2024, which is targeted to fall to 8.74% in 2024, and 6.94% in 2030. The prevalence of child marriage in Central Sulawesi is 31.91% and Sigi Regency has the third highest prevalence of child marriage, namely aged 10-14 years (0.04%) and aged 15-19 years (2.58%). Aims: To evaluate the impact of providing health education via comic media on adolescent knowledge regarding the age of marriage at SMA Negeri 1 Sigi. Method: The design applied in this research was experimental with pretest-posttest and a control group setup. Twenty-six  participants were chosen through random sampling and allocated to either the intervention group (comic media education) or the control group (leaflet media education). The research instrument utilized was a questionnaire. Data analysis was conducted using the Wilcoxon and Mann-Whitney tests. Results: This study shows that, in the control group, knowledge before education was mostly in the sufficient category (42%) and after education increased to good category (74.2%). Meanwhile, in the intervention group, before education, the majority was in the poor category (35.5%) and after education the majority was in the good category (96.8%), with a p value of 0.000 <0.05. Conclusion: Using comics proves more efficacious in enhancing teenagers' knowledge compared to utilizing leaflets. It is hoped that schools and health centers can collaborate to establish youth counseling centers as a platform for counseling students and can utilize comics as one of the educational media.